Gender differences in pharmacokinetics and pharmacodynamics of methadone substitution therapy - Graziani, Manuela; Nisticò, Robert (Frontiers in Pharmacology, 2015)
Gender-related differences in the pharmacological effects of drug are an emerging topic. This review examines gender differences in both pharmacokinetic and pharmacodynamic aspects of methadone, a long-acting opioid agonist that is prescribed as a treatment for opioid dependence and the management of chronic pain. Method: We performed a search in the Medline database from 1990 to 2014 in order to find published literature related to gender differences in pharmacokinetics and pharmacodynamics of methadone. Results: None of the studies were carried out with the primary or secondary aim to identify any gender differences in the pharmacokinetic profile of methadone. Importantly; high inter-subjects variability in PK parameters was found also intra female population. The reported differences in volume of distribution could be ascribed to the physiological differences between men and women in body weight and composition, taking into account that the dose of methadone was established irrespective of body weight of patients (Peles & Adelson, 2006). On the other hand, the few studies present in literature found no gender difference in some direct pharmacodynamic parameters. Some reports have suggested that female gender is associated with an increased risk for long-QT (LQT)-related cardiac arrhythmias in methadone maintenance subjects. Conclusion: Even though it may be too simplistic to expect variability only in one parameter to explain inter-individual variation in methadone response, we believe that a better knowledge of gender-related differences might have significant implications for better outcomes in opioid dependence substitution therapy in women.